so since you have (2x+4)^2 and (2x+6)^2. Your first job is to take this solve and uncoil these two expressions first.
(2x+4)^2 can be solved using the squared for formula.
(a+b)^2 = (a^2 + 2*a*b + b^2) = (a+b) * (a+b)
Therefore (2x+4)^2 = (2x)^2 + 2*2x*4 + (4)^2
= 4x^2 + 16x + 16
and Therefore (2x+6)^2 = (2x)^2 + 2*2x*6 + (6)^2
= 4x^2 + 24x + 36
Now that those polynomials are taken cared we have to put all together in the solution:
x^2 + 4x^2 + 24x + 36 = 4x^2 + 16x + 16.
Its better to put everything to one side and make it equal to zero.
so, x^2 + 4x^2 + 24x + 36 - (4x^2 +16x +16) = 4x^2 + 16x + 16 - ( 4x^2 + 16x + 16)
x^2 + 4x^2 + 24x + 36 - 4x^2 -16x -16 = 0
group the x^2 with each other and add them and do the same for the x's and the numbers.
so, x^2 + 4X^2 - 4x^2 + 24x - 16x + 36 -16 = 0
then you have, x^2 + 8x + 20 = 0
Now solve this equation using factorization or the quadratic equation.
reply to this comment if you need further help.